Prenatal exposure to per- and polyfluoroalkyl substances and infant growth and adiposity: the Healthy Start Study. (October 2019) - Starling, Anne P.; Adgate, John L.; Hamman, Richard F.; Kechris, Katerina; Calafat, Antonia M.; Dabelea, Dana
Abstract: Background: Prenatal exposures to certain per - and polyfluoroalkyl substances (PFAS) have been linked to lower weight and adiposity at birth but greater weight and adiposity in childhood. We hypothesized that faster growth in early infancy may be associated with maternal PFAS concentrations. Methods: Among 415 mother-infant pairs in a longitudinal cohort study, we estimated associations between maternal pregnancy serum concentrations of six PFAS and offspring weight and adiposity at ~5 months of age, and growth in early infancy. Linear and logistic regression models were adjusted for potential confounders including maternal pre-pregnancy body mass index. Effect modification by infant sex was evaluated. We evaluated potential confounding by correlated exposures via multipollutant linear regression and elastic net penalized regression. Results: Associations between maternal PFAS concentrations and infant weight and adiposity differed by offspring sex. In male infants, maternal perfluorooctanoate and perfluorononanoate were positively associated with adiposity, with percent fat mass increases of 1.5–1.7% per ln-ng/mL increase in PFAS (median adiposity at ~5 months: 24.6%). Maternal perfluorooctane sulfonate (PFOS) and perfluorohexane sulfonate (PFHxS) were associated with lower weight-for-age z-score among female infants only (−0.26 SD per ln-ng/mL PFOS, 95% CI −0.43, −0.10; −0.17 SD per ln-ng/mL PFHxS, 95% CI −0.33, −0.01). In analyses pooled by sex, 2-( N -methyl-perfluorooctane sulfonamido) acetate above vs. below the limit of detection was associated with greater odds of rapid growth in weight-for-age (odds ratio [OR] 2.2, 95% CI 1.1, 4.3) and weight-for-length (OR 3.3, 95% CI 1.8, 6.2). Multipollutant models generally confirmed the results and strengthened some associations. Discussion: We observed sex- and chemical-specific associations between maternal serum PFAS concentrations and infant weight and adiposity. Multipollutant models suggested confounding by correlated PFAS with opposing effects. Although maternal PFAS concentrations are inversely associated with infant weight and adiposity at birth, rapid gain may occur in infancy, particularly in fat mass. Highlights: Associations between maternal PFAS and infant weight and adiposity differed by sex. Prenatal PFOA and PFNA were associated with greater 5-month adiposity in males. Prenatal PFOS and PFHxS were associated with lower weight-for-age in females. MeFOSAA was associated with greater odds of rapid growth from 0 to 5 months of age.